(untitled) (Foro de Educacion, 2020)
The purpose of this paper is to emphasize the importance of «inculturation» in the religious images drawn by Monica Liu (Ho-Pei), a unique artist who promoted Religious Art and Education in Taiwan. Monica Liu adopted Western Christianity into Chinese art to create paintings that reflect her love for nature as well as Our Lady who is deeply venerated in the Catholic Church and regarded as the mother of humanity. This paper is a qualitative research based on an interview conducted with Huang Wan-Yun, a protégée of Monica Liu who had a very close relationship with the latter during the last ten years of her life. This research is also based on some writings that Monica left behind and several articles written about her by acquaintances. The culture and faith expressed by Monica Liu through Our Lady’s images help us to deeply understand the value and relationship between religious art and faith. In addressing the needs of the secular world, religious art has encountered difficulties in terms of contemporary aesthetics. Monica’s distinct aesthetic considered «moral virtues» important to modern or contemporary art and their absence could result in distorted values. Therefore, true mission work in the field of religious art has to be close to everyone’s heart, as well as emphasize the importance of inculturation through natural representations and create awareness of taboo in art, which involves «additional and supplementary» elements in original artworks.